Pembelajaran Kitab Abdul Alim Wal Muta’Allim Karya KH. M. HASYIM ASY’ARI Dalam Penanaman Etika Belajar Santri Pondok Pesantren Hidayatul Mubarok Bandar Mataram Lampung Tengah - Binti Muthmainah (DIMAR: Jurnal Pendidikan Islam, 2019)
Islam is very concerned about all aspects of human beings, ranging from the smallest things to the great things. Both those relating to God and with humans. This lack of ethics in learning makes the attention of all parties. Learning ethics has been formulated on the function and purpose of education for the future of the nation. Book of Adab al-'Alim wa al-Muta-'allim This book is a book of morals that much studied and practiced as a guide cottage. The type of research is field research. The nature of this research is descriptive research Sources of data in this study is divided into two kinds, namely primary sources and secondary sources. Informants are important objects in a study. Data collection techniques with observation, interviews and documentation. Test the validity of data with tri angulation. While data analysis with data reduction, presentation of data withdrawal and verification. The results showed that .1) Learning contents of the book Adabul Alim Wal Muta'allim, ie learning offered by Hashim Ash'ari is a learning-based ethics of learning santri who are dipenanaman ethics learn santri, 2) The obstacles encountered in the planting of ethical learning santri constraints, perhaps when explaining it sebahagian santri who do not really care about the ethics of learning, practical things such as daily practice does not go in the material. System Pondok Pesantren Hidayatul Mubarok is less supportive in the ethics of student learning santri so santri when asked the meaning of so many things that must be taught and memorized so as to burden the santri. 3) Efforts to overcome learning obstacles in the book Adabul Alim Wal Muta'allim in Pondok Pesantren Hidayatul Mubarok this done